The use of stable isotopes to investigate the effects of supplemental lysine and methionine on protein turnover and amino acid utilization in pacu, Piaractus mesopotamicus, juveniles - Abimorad, Eduardo Gianini; Ducatti, Carlos [UNESP]; Castellani, Daniela; Jomori, Rosangela Kiyoko; Portella, Maria Celia [UNESP]; Cameiro, Dalton Jose [UNESP] (Elsevier B.V., 2014)
The present study investigated the use of the stable isotope technique to evaluate the effects of nutritionally deficient diets, supplied or not with lysine and/or methionine, on the isotopic turnover of bio-elements (carbon and nitrogen) in the muscle tissue of pacu juveniles. In addition, it evaluated the contributions of growth rate (k) and metabolic rate (m) to isotopic turnover. Fish with initial weight of 10 g were fed 4 experimental diets for 100 days: a nutritionally deficient diet without amino acid supplementation (AAd) or supplemented with lysine (Lys), methionine (Met) and lysine-methionine (LysMet). During this period, muscle samples were taken from the fish to analyze isotopic signature and calculate delta C-13 and delta N-15 turnover rates. Fish fed Lys and LysMet diets exhibited higher weight gain, growth rate, feed consumption and apparent feed conversion (P < 0.05) than fish fed AAd. Fish supplemented with Met displayed intermediate growth performance. The exponential model applied indicated that fish fed Lys and LysMet diets had the lowest turnover rates and discrimination factors (A), particularly for delta N-15. Lower half-life for delta N-15 was observed in fish fed AM and Met diets. As indicated by the stable isotope technique, dietary lysine supply reduces muscle protein catabolism (m) and improves growth (k) in pacu juveniles fed plant protein-based diets. Therefore, we proved that the stable isotope technique, particularly N-15, is a useful tool in nutritional studies, providing information on isotopic turnover rates. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Plant protein; Supplementation; Deficiency; Amino acid; Protein degradation; Muscle